Comparative effects of different types of soy products on glycemic control and insulin sensitivity: a network meta-analysis of randomized controlled trials - Luo, Qiuping; Kang, Baoguo; Lei, Lifu; Yan, Hongjia; Chen, Mengting; Peng, Ting; Ouyang, Yuanlian; Sun, Hailan; Hui, Suocheng (Frontiers in Nutrition, 2026)
Background and aimsAccumulating evidence has demonstrated the benefits of soy and its extracts on glycemic control and insulin sensitivity. We hypothesized that different soy components might exhibit differentiated blood glucose and insulin sensitivity regulation effects. The goal of this network meta-analysis of randomized clinical trials (RCTs) was to estimate and rank the relative effects of soy and its extracts on glycemic control and insulin sensitivity.MethodsWe performed a strategic literature search of PubMed, Embase, and the Cochrane Library for relevant RCTs. Random-effects network meta-analyses, ranking analyses based on surface under the cumulative ranking curves (SUCRAs), and sensitivity analyses based on potential sources of heterogeneity were performed. We registered the study protocol at PROSPERO (no. CRD42022345831).ResultsSixty-one RCTs enrolling 4,744 participants were included in the quantitative analysis. In random-effects network meta-analyses. Whole soy was ranked as the best diet (SUCRA: 91.0%) regarding fasting glucose-lowering effects, with isolated isoflavones was ranked as second (SUCRA: 79.1%). For fasting insulin regulation, the best soy component choices was whole soy (SUCRA: 95.4%) and isolated isoflavones (SUCRA: 74.7%). For HOMA-IR regulation, the best soy component choices was whole soy (SUCRA: 83.4%) and Soy protein + isoflavones (SUCRA: 83.3%). No soy products showed significant effect on regulating glycated HbA1c.ConclusionsThese findings highlight that different soy components exhibit distinct effects on regulating blood glucose and insulin sensitivity. In this network meta-analysis, whole soy and isolated isoflavones were identified as potentially superior choices for improving blood glucose control and insulin sensitivity compared with other soy products.Systematic review registrationhttp://www.crd.york.ac.uk/ PROERO, identifier CRD42022345831.